Prevention aid new norm / Mohamad Daniel Imran Mohd Safar and Norarifah Ali - Mohd Safar, Mohamad Daniel Imran; Ali, Norarifah (Faculty of Art and Design, 2021)
The World Health Organization (WHO) declared the outbreak of Coronavirus Novel 2019 or COVID-19 as a worldwide pandemic on 11 March 2020. The declaration states that all countries are affected and are potentially seen as red flags and Malaysia is no exception as one of the countries in Southeast Asia that is affected by COVID-19. Therefore, to overcome the spread of this novel virus, strategic action plans as well as preventive measures need to be taken. (A.Y.A. Bakar & S. Ramli, 2020). Due to the ongoing pandemic, it has changed the way of life to new norms among the society. When we observe and do research on the pandemic issues, we are able to predict and glimpse at the future as well as learn how society is evolving, from living to working habits, from travel to consumption behaviors, from human to technological interactions. Those are the areas that can be taken into consideration in the new norm. For this purpose, I have implemented a New Norm Prevention Aid. The problem with this project is designing an elastic base for the trolley mall to prevent the spread of covid-19 for adults. Currently, there is no suitable product for trolley malls to help prevent the spread of covid-19. Therefore, Prevention Aid New Norm is a product that can be used to help prevent the spread of covid-19 through direct skin contact. The main target of this product is the trolleys used at shopping malls. The Prevention Aid New Norm serves as a trolley holder to the trolleys at the mall. Other additional functions, it can also be used as a tool to open doors and also to press buttons such as the ATM machine buttons. And, there is no product suitable for mall trolleys. The design criteria must be elastic, comfortable and safe. The target user is the users of the mall.